Mineral and textural-structural features of the ore facies of Yubileynoye massive sulfide deposit (the Southern Urals) - A. S. Tseluyko; V. V. Maslennikov; N. R. Aupova; S. P. Maslennikova (Известия высших учебных заведений: Геология и разведка)
A study of the ore facies of the massive sulfide ores from the Yubileynoe deposit (ore body № 2) has been shown. The sub-seafloor and seafloor hydrothermal, biogenic, clastic and seafloor hypergenic facies have been diagnosed in the studied ores, reflecting different formation conditions within the ore body № 2. The seafloor and sub-seafloor hydrothermal facies occur in the central part of the ore body, while clastic with seafloor hypergenic facies dominate at the flanks of the ore body. Rare minerals are native gold, minerals of Ag, Te, Bi and Pb widespread in seafloor hydrothermal and clastic ore facies. The ratio of the ore facies in the ore body № 2 shows the simiiar ore-forming processes within the Yubileynoe deposit and other massive sulfide deposits of the Urals.